Rumours of Mau Mau in Northern Rhodesia, 1950 – 1960 - Gewald, Jan-Bart (Afrika Focus, 2009)
In 1950s Northern Rhodesia, present day Zambia, rumours abounded amongst the African population intimating that the white settlers and administration were extensively involved in witchcraft, cannibalism and blood-sucking. In turn, members of the white settler community believed very much the same with regard to the African population of the territory. The development of nationalist politics and the increasing unionization of African workers in colonial Zambia led to agitation that was matched with increasing disquiet and fears on the part of white settlers. The emergence of ‘Mau Mau’ in Kenya and rumours of ‘Mau Mau’ in Northern Rhodesia served to underscore European settler fears in Northern Rhodesia. Based on research in the National Archives of Zambia and Great Britain, this paper explores the manner in which public rumour played out in Northern Rhodesia and gave emphasis to settler fears and fantasies in the territory. Key words: Mau Mau, Northern Rhodesia, colonial rule, rumours, Zambia